ANALISIS KARAKTER TOKOH DALAM NOVEL CINTA 3 BENUA KARYA FARIS BQ DAN ASTRID TITO - Nuzulul Rahmah; Antonius Totok Priyadi; Christanto Syam (Universitas Tanjungpura, 2021)
AbstractThis research aims at describing the characters in the novel Cinta 3 Benua by Faris BQ and Astrid Tito, describe how the author describes the character to the character, and to know the implementation of the character in the learning process of Bahasa Indonesia at senior high school / MA. The research method used descriptive method with a qualitative form of research. The approach used structural approach. The source of this research data is the novel Cinta 3 Benua by Faris BQ and Astrid Tito. The techniques and data collection tools used in this research are the study of documenters and researchers themselves. Data validity testing techniques used persistence of observation, triangulation, and adequacy of references. The results of this research on character characters contained in the novel Cinta 3 Benua by Faris BQ and Astrid Tito on data analysis are done by looking at the characters owned by the main characters and auxiliary characters who play an active role in the novel, as well as the way the author describes the character to the character analytically or directly through the technique of using the character's name, character appearance technique, and the author's speech technique. Dramatically or indirectly, namely through the taknik of the character, the technique of the character's deeds, the technique of the reaction of the character, and the rekasi technique of other characters. The implementation of the characters contained in the novel for Indonesian language learning is seen from aspects of curriculum, learning objectives, selection of teaching materials, and level of readability worthy of being used as learning materials for ninth grade students of Senior High School / MA.Keyword: Character, Novel, The characters